2019
DOI: 10.1038/s41385-019-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin-mediated activation of IL-33-ST2 signaling by a pathobiont promotes intestinal fibrosis

Abstract: Intestinal fibrosis is a severe complication in patients with Crohn’s disease (CD). Unfortunately, the trigger leading to the development of intestinal fibrosis in the context of CD remains elusive. Here, we show that colonization by a CD-associated pathobiont adherent-invasive Escherichia coli (AIEC) promotes the development of intestinal fibrosis. Exogenously inoculated AIEC strain LF82 and commensal E. coli HS were gradually eradicated from the intestine in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 41 publications
2
51
0
Order By: Relevance
“…Although it is known that the growth efficiency of E. coli in general is very poor when L-serine is the sole carbon source 21 , specific strains of E. coli might utilize L-serine more efficiently than others. In this regard, we have reported that LF82 exploits intestinal inflammation caused by Salmonella Typhimurium to promote its fitness, whereas commensal E. coli HS fails to do so 22 . We theorized that this phenotype is explained by variability in the efficacy of L-serine utilization between those two strains.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is known that the growth efficiency of E. coli in general is very poor when L-serine is the sole carbon source 21 , specific strains of E. coli might utilize L-serine more efficiently than others. In this regard, we have reported that LF82 exploits intestinal inflammation caused by Salmonella Typhimurium to promote its fitness, whereas commensal E. coli HS fails to do so 22 . We theorized that this phenotype is explained by variability in the efficacy of L-serine utilization between those two strains.…”
Section: Resultsmentioning
confidence: 99%
“…70 The blockade of IL-33/ST2 signaling by anti-ST2 blocking antibody significantly ameliorated intestinal fibrosis induced by co-infection of AIEC and Salmonella, which suggests a novel anti-fibrotic therapy targeting fibrogenic bacteria and its downstream signaling. 70 In addition, serum antibody to flagellin (anti-CBir1 flagellin), which shows an aberrant adaptive immunity to luminal commensal bacteria, is significantly increased in CD patients. 71 Serum anti-CBir1 expression was independently associated with complicated CD including fibrostenotic diseases.…”
Section: Role Of Gut Microbiomementioning
confidence: 92%
“…Preliminary evidence showed that the TLR5 ligand flagellin, which exists on nearly all flagellated bacteria, promotes ECM production and proliferation of fibroblasts [ 68 , 69 ]. Recently, flagellin from adherent-invasive Escherichia coli (AIEC), which is frequently isolated from the ileal tissue of CD patients and may contribute to the development of CD, was able to lead to intestinal fibrosis by binding to TLR5 expressed in intestinal epithelium, which subsequently induce the expression of IL-33 and its receptor (ST2), leading to the production of IL-13 and TGF-β in intestinal epithelial cells or T cells [ 70 ]. The blockade of IL-33/ST2 signaling by anti-ST2 blocking antibody significantly ameliorated intestinal fibrosis induced by co-infection of AIEC and Salmonella , which suggests a novel anti-fibrotic therapy targeting fibrogenic bacteria and its downstream signaling [ 70 ].…”
Section: Mechanisms Of Fibrostenotic Stricturementioning
confidence: 99%
See 1 more Smart Citation
“…Darfeuille-Michaud and colleagues defined any mucosa-associated E. coli strain as AIEC based solely upon in vitro characteristics, including survival and replication inside the mouse macrophage cell line J774, production of high levels of the pro-inflammatory cytokine TNF-α from infected J774 macrophages 32 and adherence and invasion in the human epithelial cell line Caco2. 21 Although a limited number of isolates classified as AIEC have been shown to cause colitis in animal models, [33][34][35][36][37] strains isolated from independent studies have not been systematically phenotyped across a common set of in vitro assays and an animal model of inflammation to determine if they share phenotypic traits related to virulence. Thus, it is unclear if strains classified as AIEC have a greater propensity to cause disease when compared to commensal E. coli found in the same ecological microhabitat.…”
Section: Introductionmentioning
confidence: 99%